UPAYA MENGATASI KECEMASAN PESERTA DIDIK DALAM MENGHADAPI UJIAN SEKOLAH MELALUI PENERAPAN TEKNIK LAYANAN BIMBINGAN KELOMPOK - Darwanto Darwanto (Universitas Pakuan, 2022)
EFFORTS TO OVERCOME STUDENT ANXIETY IN FACING SCHOOL EXAMS THROUGH THE APPLICATION OF GROUP GUIDANCE SERVICE TECHNIQUESThe purpose of this study was to determine the application of group guidance service techniques to overcome students' anxiety, to describe the process of efforts to overcome student anxiety, to measure the increase in efforts to overcome students' anxiety in dealing with school exams by applying group guidance service techniques in class IX of junior high school. The problem of this research is the high anxiety of students in facing the School Exam, therefore researchers will try to overcome this anxiety through the application of group guidance service techniques in the hope that students are able to overcome all the problems they experience in facing the School Exam. The method used is action research specifically on the problem of efforts to overcome student anxiety in facing school exams. The data collection technique used is filling out a questionnaire. Observation, interview. The tools used in this research are related to action planning, implementation process, as well as the results of the implementation of the action, the unit of guidance and counseling services in the field of tutoring and group guidance services. observation guidelines, to collect data at the time of the implementation of the good actions concerning the activities of teachers and students as research subjects. The results showed that the implementation of guidance and counseling action research with a group guidance service approach could reduce students' anxiety levels in facing the School Exam in class IX of Bogor City Junior High School. The existence of the ability of students in an effort to reduce the level of anxiety of students in facing school exams and is supported by the active involvement of students in the implementation of group guidance. The magnitude of the ability of students in an effort to reduce the level of anxiety of students in facing the School Exam is the lowest score in the pre-cycle, which is 70, decreasing to 39 in the first cycle and 22 in the second cycle. The highest value in the pre-cycle was 99, decreased to 78 in the first cycle and decreased again to 40 in the second cycle. The average in the pre-cycle was 81.50 in the first cycle changed to 56.71 in the second cycle and 31.43 in the second cycle. The completeness value becomes 100% because all students who are the subjects of the study have a score below or equal to the completeness target, which is 40.